Kauṇḍinya in Southeast Asia revisited - Golzio, Karl-Heinz (Journal of Global Archaeology, 2023)
This paper revises earlier interpretations of the history of the figure of Kauṇḍinya and his spouse Somā in South-east Asia. While it was assumed so far – also by the author of this contribution – that the Kauṇḍinya mentioned in the inscription C. 96 was a figure from mythical ages, in this contribution a different reading of the sources is proposed. It is argued, that the inscription relates the pair in question to Bhavapura, the capital of Bhavavarman I and that chronologically, they must have been contemporaries of Īśānavarman (the king who ruled between ca. 616 to ca. 637 in Northern Cambodia) as it was their son Candravarman who was married to the granddaughter of the latter. The occurrence of the name Kauṇḍinya in other historical contexts is also examined in detail, highlighting the need for a more critical reading of the sources.